Analyzing Supply Chain Risks Using the House of Risk Method: Evidence from the Salt Industry in Padang City - Ahmad Syafruddin Indrapriyatna; Tessa Zulenia Fitri; Rahmat Budiarto (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2026)
Salt remains an important commodity for households and food-related businesses in Indonesia. In Padang City, the availability of salt can be affected when problems occur in raw material procurement, processing, or distribution. Such problems may also make daily activities more difficult for the actors in the chain. Although these risks are often encountered in practice, their priority in the local salt industry has not been systematically studied. This study applies the House of Risk (HOR) method to analyze supply chain risks in the salt industry of Padang City. The data were collected using questionnaires distributed to actors involved in procurement, processing, and distribution. These respondents were included because they handle the activities directly and understand the problems that appear in day-to-day operations. The analysis considers the severity of risk events, the occurrence of risk agents, and the relationship between risk events and their causes. These values were then used to calculate the Aggregate Risk Potential (ARP), which served as the basis for prioritizing risks. The findings show that risk exposure is mainly concentrated in procurement and production activities. This means that mitigation efforts should give more attention to these two stages. Preventive actions were then compared by looking at two practical considerations: how useful each action was expected to be and how difficult it would be to apply. The analysis shows that a small number of risk agents make a major contribution to the overall risk exposure. For this reason, these agents should be handled first. This order of action can help the actors reduce the most important risks without making the supply chain too rigid when conditions change.